Inhibition of Neuronal Nitric Oxide Synthase and Soluble Guanylate Cyclase Prevents Depression-Like Behaviour in Rats Exposed to Chronic Unpredictable Mild Stress - ARICIOĞLU, FEYZA (WILEY, 2012)
Depression is the most common psychiatric disorder. It is well established that endogenous nitric oxide (NO) contributes to chronic unpredictable mild stress (CUMS)-induced depression. The aim of this study was to investigate brain-derived neurotropic factor (BDNF) expression in CUMS-induced depression-like behaviour in rats. Rats were exposed to CUMS for 5 weeks. A specific and selective nNOS inhibitor, 3-bromo-7-nitroindazole (3-Br-7-NI; 20 mg/kg/day, i.p.), and a specific soluble guanylate cyclase (sGC) inhibitor, 1H-(1,2,4)oxadiazolo(4,3-a)quinoxalin-1-one (ODQ; 10 mg/kg/day, i.p.), were administered during CUMS. The forced swimming test (FST) was used to assess despair and sucrose consumption, and sucrose preference test was used to assess anhedonia that are the main symptoms of the depression. We show that both 3-Br-7-NI and ODQ administration during CUMS suppressed CUMS-induced, depression-like behavioural changes, including reduced sucrose preference, body-weight and locomotor activity as well as increased immobility time in the FST. CUMS also significantly decreased BDNF protein levels in the CA1 and CA3 regions of the hippocampus, which was reversed by 3-Br-7-NI and ODQ administration. Our findings suggest a novel role for nNOS and sGC-cGMP in the development of the CUMS model of depression.
Keywords: ANTIDEPRESSANT-LIKE; NEUROTROPHIC FACTOR; POTENT INHIBITORS; METHYLENE-BLUE; LIFE EVENTS; REDUCTION; MICE; BDNF; HIPPOCAMPUS; INVOLVEMENT